2021
DOI: 10.1101/2021.10.15.21265063
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with severity of COVID-19 disease in a multicenter cohort of people with HIV in the United States, March-December 2020

Abstract: Background: Understanding the spectrum of SARS-CoV-2 infection and COVID-19 disease in people with HIV (PWH) is critical to provide clinical guidance and implement risk-reduction strategies. Objective: To characterize COVID-19 in PWH in the United States and identify predictors of disease severity. Design: Observational cohort study. Setting: Geographically diverse clinical sites in the CFAR Network of Integrated Clinical Systems (CNICS) Participants: Adults receiving HIV care through December 31, 2020. Measur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…For example, CNICS developed an extensive case ascertainment protocol for COVID-19 based on rapidly evolving diagnoses, expanding laboratory criteria, and complemented this with verification both to confirm the cases as well as to validate and better understand different ascertainment criteria and how they varied by site and over time. A recent CROI presentation 27 described the first 198 COVID-19 cases identified among 13,862 PWH and found increased risk among women, PWH who were Black or Hispanic, and those with a body mass index > 30. Among PWH with COVID-19, the relative risk of being hospitalized was 2-fold higher among PWH aged 60 years and older.…”
Section: Lesson 3: Timely Datamentioning
confidence: 99%
“…For example, CNICS developed an extensive case ascertainment protocol for COVID-19 based on rapidly evolving diagnoses, expanding laboratory criteria, and complemented this with verification both to confirm the cases as well as to validate and better understand different ascertainment criteria and how they varied by site and over time. A recent CROI presentation 27 described the first 198 COVID-19 cases identified among 13,862 PWH and found increased risk among women, PWH who were Black or Hispanic, and those with a body mass index > 30. Among PWH with COVID-19, the relative risk of being hospitalized was 2-fold higher among PWH aged 60 years and older.…”
Section: Lesson 3: Timely Datamentioning
confidence: 99%
“…A WHO report, based on surveillance data from 37 countries between 01 January 2020 and 29 April 2021, demonstrated that PLWH hospitalized with COVID-19 had an increased risk of severe disease and in-hospital mortality than people without HIV [23]. For PLWH with severe immunosuppression or uncontrolled HIV viraemia, fatality rates for COVID-19 remain uncertain [19,20,24,25], although recent evidence suggests that these individuals have a higher risk of severe COVID-19 disease [26,27]. Similarly, a higher risk of complications from COVID-19 has been reported among PLWH with a low CD4 + T cell count nadir prior to ART initiation compared to those with higher nadirs [28].…”
Section: Introductionmentioning
confidence: 99%